Analysis of the Role of Social Media in Shaping GEN Z's Political Literacy in the 2024 General Election - Rahmadani, Deni; Hidayat, Cecep (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The 2024 General Election marks a significant turning point in Indonesia's political landscape, particularly with the rising participation of Generation Z as first-time voters. This generation is highly connected to social media, which serves as their primary source of political information. This study highlights the urgency of understanding how social media influences the political literacy of Gen Z, given their vulnerability to misinformation and digital propaganda. Theoretically, this research is grounded in the concept of political literacy, which encompasses the ability to comprehend political systems, think critically about information, and engage in political processes. A qualitative approach was employed using a literature review method to examine the impact of social media on Gen Z's political understanding and attitudes. The findings reveal that social media plays a significant role in shaping the political behavior and attitudes of young people, particularly through its fast-paced and interactive communication. Social media also serves as a platform for discussion and opinion formation, which can enhance political participation. However, challenges such as the spread of hoaxes and opinion polarization remain substantial obstacles. Therefore, it is essential to strengthen media literacy and political education so that Generation Z can become critical and rational voters. This study offers strategic recommendations for policymakers, educators, and society to positively leverage the potential of social media in supporting democratic development.